Atomic substitution effects of inorganic perovskites for optoelectronic properties modulations. Issue 4 (16th March 2022) - Chen, Baian; Sun, Mingzi; Chen, Rui; Huang, Bolong
Abstract: Inorganic perovskites exhibit impressive optoelectronic properties through experimental doping or composition modification. However, the underlying mechanism of the atomic substitution effect needs to be elucidated to guide future device optimizations. In this work, we have carried out systematic research on a series of inorganic perovskites regarding their electronic, optical, and vibrational properties. The band structures are strongly affected by the B‐sites. Meanwhile, phonon dispersions have revealed that the peculiar energy band offset is determined by the varied orbital and bonding characteristics. In addition, optical properties are directly influenced by the bond lengths between B‐sites and halogens, which are regulated by atomic substitutions. In addition, the infrared active spectrum and corresponding vibration modes indicate that the metal‐halogen octahedrons were confirmed to be the main source of these vibration modes. This work reveals the atomic substation effects of inorganic perovskites, which offer significant guidance for the design of next‐generation optoelectronic devices. Abstract : Inorganic perovskites have attracted extensive attention in recent years because of their promising potential in photoelectronic devices. In this work, the mechanism of atomic substitution induced variations in electronic, optical, and vibrational properties of inorganic perovskites are analyzed by applying theoretical computation. This research can provide significant guidance for the design of next‐generation optoelectronic materials